Predictors of neonatal mortality in Assosa zone, Western Ethiopia: a matched case control study - Fillmon Kidus (BMC Pregnancy and Childbirth, 2019)
Abstract Background Benshangul Gumuze region is one of the regional states in Ethiopia, with highest rate of neonatal mortality rate. The trend increased at alarming rate from 42/1000 live birth in 2005 to 62/ 1000 live birth in 2011. Hence, identifying predictors of neonatal death and implement evidence based interventions at community level is crucial to reduce the mortality. Therefore, the purpose of this study was to identify predictors of neonatal mortality in Assosa zone, Western Ethiopia. Methods A community based matched case control study was conducted from February 1, until December 30, 2013. The study included 114 cases who died during the first 28 completed days after birth from September 1, 2010 till September 1, 2013. For each case, one alive control matched approximately by the same date of birth (−/+ 2 days) was identified from the preliminary data collected. Finally, multivariate conditional logistic regression analysis was performed; and goodness of fit of the final model was tested using likely hood ratio test. All analysis was done using EPI Info version 7 and SPSS version 16 statistical softwares. Results Model households in health extension packages [AmOR = 0.32; 95%CI:0.12–0.86], age at first pregnancy < 20 years old [AmOR = 4.3;95%CI: 1.13–16.27],pregnancy complication [AmOR = 4.59; 95%CI: 1.53–13.78], delivery complication [AmOR = 2.80; 95%CI: 1.06–7.39], antenatal care visit [AmOR = 0.34;95%CI: 0.12–0.94], primipara mothers [AmOR = 3.37; 95%CI:1.05–10.78], small size neonate at birth [AmOR = 3.40: 95%CI: 1.05–11.55], gestational age < 37 weeks [AmOR = 4.35;95%CI:1.16–16.28], and home delivery [AmOR = 2.84; 95%CI:1.07–7.55] were found statistically significantly associated with neonatal mortality. Conclusions Model households in health extension package and antenatal care visit were associated with reducing risk of neonatal mortality. However, age at first pregnancy < 20 years old, primipara mothers, pregnancy complication, delivery complication, small size neonates, gestational age < 37 weeks, and home delivery were associated with increasing risk of neonatal death. Therefore, promotion of model household in health extension package, anti natal care visit, institutional delivery, family planning to prevent early age pregnancy; and improve access to basic emergency obstetric care and intensive newborn care centers are effective interventions to reduce risk of neonatal mortality at community level.